Cálculo de índices espectrales para el área del Delta del Río San Juan, Bahía Málaga y Bahía de Buenaventura, a partir del uso de imágenes de PlanetScope en Google Earth Engine (2023)
The purpose of this work is to calculate four spectral indices for a 342 km2 area located between the San Juan River Delta, Málaga Bay and the Buenaventura Bay using the Google Earth Engine platform. The study was based on the use of 21 PlanetScope satellite images from 2023, which were obtained through the connection PlanetScope and GEE using an API KEY and stored on the Google Cloud Platform